Antimicrobial effect of copper surfaces on bacteria isolated from poultry meat - Parra, Angel (Braz J Microbiol, 2018)
Poultry meat is a food product that usually carries high rates of microbial contamination, including foodborne pathogens. The poultry industry has established different systems to minimize these hazards. In recent years, extensive literature has demonstrated the antimicrobial activity of different contact surfaces made of copper to effectively reduce microbial loads. The aim of the present study was to evaluate the antibacterial effect of copper surfaces on the transmission of two foodborne pathogens – Salmonella enterica and Listeria monocytogenes – and a poultry native microbiota bacterial species – Enterobacter cloacae. We also evaluated the impact of the poultry meat matrix on the antimicrobial activity of a copper surface. Our results indicated that copper surfaces reduced the bacterial load quickly (<than 4 min) when the microorganisms were exposed to polished copper surfaces. Even when bacteria were inoculated on copper surfaces soiled with the organic matrix (washing water from poultry carcasses) and survival rates were significantly higher, an antimicrobial effect was still observed. Survival rates of two microorganisms simultaneously exposed to copper did not show significant differences. We found an antimicrobial effect over pathogenic and non-pathogenic microorganisms. Results suggest a potential role for copper surfaces in the control of microbiological hazards in the poultry industry.